Analisis Persepsi Pelanggan Atas Dimensi Kualitas Jasa Terhadap Kepuasan Pelanggan Dan Niat Beli Ulang - Wulandari, Kartika (Jurnal Administrasi Bisnis, 2015)
The aim of this research is to examine the impact of customers perception of the service quality dimention to the customer satisfaction and to examine the impact of customer satisfaction of WADWAXs service quality to the customer repurchase intention. One hundred respondents are collected by purposive sampling method with a criteria that is the customer have used auto salon polish service in WADWAX in the period of January 2011 to August 2014 at least twice a year. A survey method had been carried out by distributing questionnaire and data are analyzed by multiple and simple regresi analyst by using SPSS 22.0 software. The result shows that WADWAX service quality has strong effects to customer satisfication with tangible and empathy are the most influencing factors. And the customer satisfication has positive effects to the customer repurchase intention in WADWAX Keywords: service quality, customer satisfaction, customer repurchase intention